2017
DOI: 10.1515/ijamh-2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevalence and contributing factors among adolescents in secondary schools in Pemagatshel district, Bhutan

Abstract: Background The prevalence of obesity has increased globally, with childhood and adolescent obesity being more common in developed countries. There has been no study on teenage obesity in Bhutan. In this study, we aimed to assess the prevalence of obesity in Bhutan for the first time in order to provide a baseline for future researchers. Methods The investigation, which included 392 adolescents, aimed to identify the prevalence of overweight and obesity and its contributing factors. Anthropometric measurements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…88 Other school environment Finally, there was one poor study of the school food environment in which we were unable to categorise the characteristics investigated as the methodology simply stated that the researchers used 10 questions to collect data on school environment without giving details of the questions. 92 This study reported no association between the 'school environment' and BMI.…”
Section: School Marketing and Regulationmentioning
confidence: 60%
“…88 Other school environment Finally, there was one poor study of the school food environment in which we were unable to categorise the characteristics investigated as the methodology simply stated that the researchers used 10 questions to collect data on school environment without giving details of the questions. 92 This study reported no association between the 'school environment' and BMI.…”
Section: School Marketing and Regulationmentioning
confidence: 60%
“…By comparison, the reported prevalence of overweight in Bangladesh, Nepal, and Thailand were 16.9%, 21%, and 28.3%, respectively [ 20 , 22 , 24 ]. Rapid urbanization, low nutrition literacy, sedentary lifestyle, and high carbohydrate and low protein diets are among the drivers of the global epidemic of overweight or obesity [ 25 27 ]. Similar to studies in other low-middle income countries, the prevalence of overweight or obesity increased with age, being female, engaging in certain occupations (e.g., homemakers or government employees), and residing in urban areas associated with physically inactive [ 20 , 22 , 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 A study conducted in eastern part of Bhutan among secondary school students reported a higher prevalence of obesity in adolescent female population. 17 On the other hand, T1DM is significantly low in CRRH, only three cases of T1DM were recorded in last 5 years at CRRH.…”
Section: Discussionmentioning
confidence: 86%